Editorial: Global Conference on Global Warming - 2011 Special Issue - Costa, Maria João (2013)
The Third “Global Conference on Global Warming” (GCGW-2011) was held in Lisbon, Portugal, from 10 to 14 July 2011, at the Calouste Gulbenkian Building. It was sponsored and organized by the Geophysics Centre of the University of Évora and included plenary sessions, keynote lectures, and several specialized sessions on different topics related to global warming and potential mitigation solutions. GCGW-2011 gathered the scientific, governmental and industrial communities from all over the world to exchange views, present new technologies and developments, and discuss future directions, strategies and priorities in a global warming scenario, namely energy use and efficiency, mitigation and adaptation strategies.